2014
DOI: 10.1242/dev.117200
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial β1 integrin is required for lung branching morphogenesis and alveolarization

Abstract: Integrin-dependent interactions between cells and extracellular matrix regulate lung development; however, specific roles for β1-containing integrins in individual cell types, including epithelial cells, remain incompletely understood. In this study, the functional importance of β1 integrin in lung epithelium during mouse lung development was investigated by deleting the integrin from E10.5 onwards using surfactant protein C promoter-driven Cre. These mutant mice appeared normal at birth but failed to gain wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 66 publications
2
33
2
Order By: Relevance
“…Our findings provide unambiguous evidence of critical non-cellautonomous roles for integrin β1 in vascular development that contrast with numerous reports of other tissue-specific integrin β1 knockouts (31)(32)(33)(34), and complement established vascular cellautonomous functions of integrin β1 (9-13). Our data support the idea that there are distinct tissue and temporal context-dependent requirements for specific integrin heterodimers in vascular development (11).…”
Section: Discussioncontrasting
confidence: 59%
“…Our findings provide unambiguous evidence of critical non-cellautonomous roles for integrin β1 in vascular development that contrast with numerous reports of other tissue-specific integrin β1 knockouts (31)(32)(33)(34), and complement established vascular cellautonomous functions of integrin β1 (9-13). Our data support the idea that there are distinct tissue and temporal context-dependent requirements for specific integrin heterodimers in vascular development (11).…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, the role of TMEFF2 in prostate regeneration could be facilitated by its effect on integrin expression via its role in metabolism. It has been described that changes in integrin expression, specifically b1, not only affect cell migration but also glandular morphogenesis in different tissues [47][48][49]. Alternative mechanisms related to the TMEFF2 signaling potential can also explain its role in prostate morphogenesis after castration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies determined that loss of the ECM and b1 integrin negatively impacts lung branching during development. Plosa et al established that epithelial b1 integrin was required throughout the different stages of lung development for airway branching morphogenesis, alveolarization, and maintenance of homeostasis (Plosa et al, 2014). However, the mechanisms of how epithelial branching and factors contributing to alveolar lumen structural formation have not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genetic manipulation of aVb3 and aVb5 integrins indicate that the aV integrin / FN interactions are not necessary for vascular formation (Hynes, 2002). During pulmonary morphogenesis, a5b1 integrin and its ECM ligand FN are expressed during lung development (Chen et al, 1986;Snyder et al, 1987;Roman and McDonald, 1992) and have been shown to be essential for lung branching morphogenesis (Sakai et al, 2003;Plosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%